Timber certification as a catalyst for change in forest governance in Cameroon, Indonesia, and Peru - Savilaakso, S.; Cerutti, P.O.; Montoya Zumaeta, J.G.; Ruslandi; Essiane-Mendoula, E.; Tsanga, R. (Informa UK Limited, 2017)
Policy instruments targeting environmental, social, and economic sustainability cover both local and global geographies and stem from both the public and private sectors. These policy instruments do not work in silos but interact throughout the regulatory process. In this paper we discuss interactions between public regulations and private certification that affect how forests are managed in three tropical countries: Indonesia, Cameroon, and Peru. We show how the governance regime in each of the countries has evolved in response to environmental and social issues. We focus on the Forest Stewardship Council's forest stewardship certification as it is the main global certification scheme in the tropical region and look at its role in attaining sustainability in timber production.Case study results from Indonesia, Cameroon, and Peru indicate that certification influences all stages of the policy process: agenda setting and negotiation; implementation, and monitoring and enforcement. Results also suggest that certification introduces positive changes in management practices and improves social and environmental performance. However, its influence in attaining broader-scale sustainability is limited by a low level of uptake, notably in tropical countries where the costs of getting certified and maintaining certification are high and the certification criteria are rather complex, as well as by some of its inherent characteristics, as it can only solve problems at the forest management unit level.EDITED BY Meine van Noordwijk